2006
DOI: 10.1080/14622200600576669
|View full text |Cite
|
Sign up to set email alerts
|

Acute nicotine fails to alter event‐related potential or behavioral performance indices of auditory distraction in cigarette smokers

Abstract: Behavioral studies have shown that nicotine enhances performance in sustained attention tasks, but they have not shown convincing support for the effects of nicotine on tasks requiring selective attention or attentional control under conditions of distraction. We investigated distractibility in 14 smokers (7 females) with event-related brain potentials (ERPs) and behavioral performance measures extracted from an auditory discrimination task requiring a choice reaction time response to short- and long-duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…More generally, there are few studies assessing nicotine's effect on focused attention, directly or indirectly via smoking, and they have produced mixed results. In deprived smokers, transdermal nicotine (Mancuso et al, 1999) and smoking (e.g., Domino & Kishimoto, 2002) increased focused attention, though similar studies found no effect using subcutaneous injection (Foulds et al, 1996) and nicotine gum (Knott et al, 2006). In non-smokers a subcutaneous injection of nicotine improved focused attention on an ERP task (Le Houezec et al, 1994).…”
Section: Early Filtering and Focused Attentionmentioning
confidence: 94%
“…More generally, there are few studies assessing nicotine's effect on focused attention, directly or indirectly via smoking, and they have produced mixed results. In deprived smokers, transdermal nicotine (Mancuso et al, 1999) and smoking (e.g., Domino & Kishimoto, 2002) increased focused attention, though similar studies found no effect using subcutaneous injection (Foulds et al, 1996) and nicotine gum (Knott et al, 2006). In non-smokers a subcutaneous injection of nicotine improved focused attention on an ERP task (Le Houezec et al, 1994).…”
Section: Early Filtering and Focused Attentionmentioning
confidence: 94%
“…In SZ, nicotine has exerted no effect on pitch deviant MMNs (Dulude et al ., ) but has shortened the latency of the intensity deviant MMN (Fisher et al ., ) and normalized the duration MMN by increasing amplitude to a level comparable to that of controls (Dulude et al ., ). In healthy volunteers, although both non‐significant (Knott et al ., , ) and diminishing amplitude effects have been observed with the pitch deviant MMN following acute nicotine administration (Knott et al ., ), this MMN has generally been found to exhibit a shortened latency (Inami et al ., , ; Dunbar et al ., ) and/or an increased amplitude (Harkrider and Hedrick, ; Dunbar et al ., ) with nicotine or nAChR agonist treatment. Nicotine has also enhanced MMN elicited by auditory pattern (Baldeweg et al ., ) and temporal (interstimulus interval) deviants (Martin et al ., ) as well as by visual deviants (Fisher et al ., ).…”
Section: Introductionmentioning
confidence: 96%
“…Strongly dependent on glutamatergic signaling, MMN is attenuated in rats, monkeys and healthy adults with high-affinity NMDA (N-methyl-Daspartate)-type glutamate receptor antagonists (Javitt et al, 1996;Tikhonravov et al 2008;Umbricht et al 2000) such as ketamine which, when combined with nicotine, fails to disrupt MMN in some but not all investigations (Mathalon et al 2014). Most frequently investigated in healthy participants with frequency deviants, nicotinic stimulation has resulted in negative (Knott et al 2006, diminishing (Knott et al 2009) and enhancing effects on MMN amplitude (Dunbar et al 2007), with the latter positive outcome also being shown with pattern (Baldeweg et al 2006), temporal (Martin et al 2009) and visual deviants . Such response variability is also seen in the relatively few studies in SZ, with nicotine not affecting frequency deviant MMN (Dulude et al 2010;Inami et al 2007), shortening latency of intensity-deviant MMN ) and in our work, "normalizing" durationdeviant MMN by increasing the diminished MMN in patients to a level comparable to that seen in healthy volunteers (Dulude et al 2010).…”
Section: Introductionmentioning
confidence: 99%